Architectural design of gas transportation automation system based on the system-type-centric method - Polataiko, Ihor; Zamikhovskyi, Leonid (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the architectural design process of a gas transportation automation system at the compressor station level as a multi-aspect heterogeneous computer-software system in the automation domain. This system integrates subsystems of different fundamental architectural natures – ranging from PLC programs to cloud-based analytical systems and information systems with operational logic. The study is focused on solving the problem of completeness, relevance, and interoperability of architectural design artifacts for complex computer-software automation systems. Existing methods predominantly focus on individual aspects – design patterns, system integration and layering, optimal control, or the implementation of specific capabilities, such as supervisory control. They do not form a single, end-to-end architectural design process for the system as a whole. The essence of the obtained results lies in the formation of an architectural model of the system through the execution of the architectural design process using a system-type-centric method. The constructed architectural model is distinguished by the traceability of architectural artifacts and the selection of architectural viewpoints depending on the fundamental nature of the systems, which ensures the coverage of fundamental architectural aspects and achieves the completeness of the architectural description. It is built through the sequential formation of system views from relevant viewpoints. The results demonstrate the scientific and practical feasibility of the method for the comprehensive design of complex heterogeneous automation systems that combine operational technology (OT) and information technology (IT) levels. From a practical standpoint, the obtained results can be applied as a reference architectural model for the implementation of the method